2016
DOI: 10.1111/sdi.12511
|View full text |Cite
|
Sign up to set email alerts
|

We Refuse to Give up on Nonmaturing Fistulas

Abstract: The nonmaturing arteriovenous fistula (AVF) is a major problem and can lead to significant patient morbidity and mortality because the patient is exposed to the risk of dialysis with a central venous catheter (CVC). Access planning should include a strategy to decrease the incidence of AVF nonmaturation. All newly created AVFs should be evaluated for maturation at 4-6 weeks. If it is judged to not be usable at that time, it should be evaluated for salvage. However, if multiple procedures over a prolonged perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Multiple reports have emphasized that percutaneous transluminal balloon angioplasty has assumed a central role in the management of arteriovenous dialysis access (graft and fistula) stenosis. [5][6][7][8][9][10][11][12][13][14][15][16][17] Over the years, this treatment has proven to be safe as well as effective. [4][5][6][7][8][9][10][11] This procedure is usually performed on an outpatient basis and the dialysis access can be used immediately following the angioplasty.…”
Section: Stenosis Of Vascular Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple reports have emphasized that percutaneous transluminal balloon angioplasty has assumed a central role in the management of arteriovenous dialysis access (graft and fistula) stenosis. [5][6][7][8][9][10][11][12][13][14][15][16][17] Over the years, this treatment has proven to be safe as well as effective. [4][5][6][7][8][9][10][11] This procedure is usually performed on an outpatient basis and the dialysis access can be used immediately following the angioplasty.…”
Section: Stenosis Of Vascular Accessmentioning
confidence: 99%
“…Mechanical as well as pharmacomechanical thrombolysis procedures can be successfully performed. 6,9,10,16 It is worth mentioning that the primary patency rates after declotting of a clotted vascular access are markedly reduced when compared with the primary patency following angioplasty of access stenosis. 10,16 Declotting of a thrombosed access should be performed quickly for multiple reasons.…”
Section: Thrombosis Of Hemodialysis Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dember et al showed that approximately 60% of new fistulas fail to attain suitability for dialysis and Lok et al demonstrated that patients at highest risk for primary failure have an overall risk of 70% . Those with primary failure undergo an average of 3.3 procedures to assist maturation and typically require an additional 3 months before the fistula is deemed suitable for cannulation …”
Section: Establishing Vascular Access Should Be Easymentioning
confidence: 99%